Understanding behavioural change: A guide for analysing factors influencing progress towards outcomes - Gibbons, S (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
This guide provides users with a way to analyse the factors that enable progress along CCAFS impact pathways, as a means to contribute to improved program planning. The approach focuses on understanding what factors are enabling or preventing the achievements of site, national and regional level outcomes. Given that development outcomes relate to changes in the behaviours of next-users, the guide provides users with an analytical framework for understanding behavioural change in relationship to CCAFS. It provides tools for gathering and analysing information on behaviours, the barriers and promoters of behavioural change, and for analysing mechanisms within the CCAFS program for enhancing and supporting positive change.